Stock de carbone dans les gros débris ligneux végétaux : cas des forêts tropicales pluvieuses de la Likouala, République du Congo - Ifo, Suspense Averti; Mbemba, Mackline; Koubouana, Félix; Binsangou, Stoffenne (European Scientific Journal, ESJ, 2017)
In order to improve the knowledge of the functioning of tropical rainfall forests in the Congo basin ,a study on the quantification of the stocks of carbon in coarse woody debris was done in Likouala’s area, in Republic of Congo. To achieve this goal,14 squares plots of 50mx50m had installed on the whole study area, including ten plots in primary forest and four in secondary forests. The method used was to make an inventory of woody debris lying on the ground or Log and snags in the different study plots. There sults of this study revealed average stocks of 603.45kg MS.ha -1 in primary forests, 468.64 kg MS.ha-1 in secondaryforestsand392.68 kgMS.ha- 1 in agroforestry, with no significant differences between stocks in primary forests and secondary forests (P = 0.05). In addition this study revealed that carbon stocks varied from one locality to another in all the study area, as well as between the experimental plots (p = 0.005). This study helps to understand that the Chablis played a key role in the production of large woody debris.